Algorithm to select chest wall perforator flaps in immediate conservative breast surgery reconstruction (Revista Argentina de Cirugía, 2026)
Background: Chest wall perforator flaps are a good option for immediate breast reconstruction after conservative surgery.Objective: The aim of this study was to describe the clinical results of an algorithm for using chest wall perforator flaps for breast reconstruction after breast-conserving surgery for breast cancer.Material and methods: We conducted a descriptive and retrospective study. The information was retrieved from the medical records of the patients diagnosed with breast cancer who underwent breast-conserving surgery and required reconstruction using chest wall perforator flaps between January 2020 and March 2022. The indications included volume deficit, contour defect and asymmetry.The vascular pedicle of the flap was evaluated by color Doppler ultrasound in all cases, which allowed us to follow an algorithm for selecting the best flap option.Results: Twenty flaps were made in 19 patients. Mean age: 52 years ± 11 (range 30-76). There were no intraoperative complications. One patient required reoperation due to a hematoma with compression of the vascular pedicle of the flap with partial flap loss, and another flap presented superficial epidermolysis. There were no cases of complete flap loss. All the patients underwent postoperativeradiation therapy without loss of volume or retractions. Mean follow-up was 15 months. At 6 months, patients rated the results as excellent, good, and fair in 7, 11, and 2 cases, respectively.Conclusion: The selection of local perforator flaps to correct breast defects after conservative surgery, using preoperative color Doppler ultrasound to identify the vascular pedicle and a specific algorithm...
Keywords: breast cancer; breast conserving surgery; segmental mastectomy; perforator flap; algorithm